Female wolf spiders exert cryptic control drastically reducing ejaculate size. (5th July 2017) - Albo, Maria J.; Costa, Fernando G.
Abstract: Sexes' roles in post‐copulatory processes have important effects on individual fitness and are promising to study in species showing complex mating behaviours. In the spider Schizocosa malitiosa, males perform two different copulatory patterns, pattern 1 includes 80% of total pedipalp insertions and pattern 2 includes 20%. Both patterns produce similar number of offspring, but pattern 1 induces higher female reluctance to remating than pattern 2. We hypothesised that the complex copulatory patterns are linked to post‐copulatory sexual selection, affecting males' sperm transfer and the resulting sperm storage by females. First, we examined amounts of sperm in males and live females from uninterrupted (pattern 1 + 2) and interrupted matings (pattern 1, pattern 2). Second, in order to disentangle male and female actions, we induced males to mate with dead females and examined amounts of sperm. Males transfer in total 71% of the sperm available in their pedipalps, being higher but not significant in pattern 1 than in pattern 2. Females drastically reduced the amount of sperm stored in their spermathecae and such control is stronger in pattern 1 compared to pattern 2 matings. We propose that cryptic female control is a main factor driving males to strengthen sperm transfer. Active female reduction in ejaculate most probably diminished her reluctance to remate.